STRATEGI KETELADANAN GURU DALAM INTERNALISASI KURIKULUM BERBASIS CINTA DI TINGKAT DASAR DI SMP N 1 MAKARTI JAYA - Pitriani; Ahmad Zainuri; Muslim Gani Yasir (STKIP Subang, 2026)
This study looks at how elementary school teachers at SMP N 1 Makarti Jaya use role-modeling techniques to help students internalize a love-based curriculum. The development of compassion, empathy, respect, accountability, and spiritual awareness are emphasized in a love-based curriculum as fundamental character traits included into regular educational activities. The study uses a case study design and a qualitative methodology. In-depth interviews with educators and school administrators, classroom observations, and document analysis were used to gather data. Thematic analysis was used to examine the data in order to find patterns of teachers' exceptional activities. The results show that internalizing the values of love in both academic and extracurricular situations is greatly aided by teacher role modeling. Teachers exhibit consistency in their words and deeds, engage in courteous communication, empathize with their students, and include moral principles into the curriculum. Value internalization is further reinforced by habituation techniques, introspective dialogues, and cooperative exercises. Through organized character-building programs, mutual respect among students, and religious activities, the school culture also promotes the execution of the love-based curriculum. The study comes to the conclusion that instructors' personal integrity and capacity to serve as genuine role models for pupils are critical to the success of a love-based curriculum. In addition to influencing students' cognitive comprehension of values, teacher exemplary also molds their attitudes and actions. Therefore, maintaining the internalization of love-based ideals in Islamic educational institutions requires enhancing teachers' character and professional growth.